Epileptic seizures in cerebral venous sinus thrombosis: Subgroup analysis of VENOST study - Uluduz, Derya; Midi, Ipek; Duman, Taskin; Yayla, Vildan; Karahan, Ali Yavuz; Afsar, Nazire; Gunes, Taskin (W B Saunders Co Ltd, 2020)
Purpose: The aim of this study is to evaluate the presence and prognostic impact of early seizures in cerebral venous sinus thrombosis patients (CVST). Method: VENOST is a retrospective and prospective national multicenter observational study. CVST patients with or without epileptic seizures (ES) were analyzed and compared in terms of demographic and imaging data, causative factors, clinical variables, and prognosis in a total of 1126 patients. Results: The mean age of the patients in the ES group was 39.73 +/- 12.64 and 40.17 +/- 14.02 years in the non-ES group (p > 0.05). Epileptic seizures were more common (76.6 %) in females (p < 0.001). Early ES occurred in 269 of 1126 patients (23.9 %). Epileptic seizures mainly presented in the acute phase (71.4 %) of the disease (p < 0.001). Majority of these (60.5 %) were in the first 24 h of the CVST. The most common neurological signs were focal neurologic deficits (29.9 %) and altered consciousness (31.4 %) in the ES group. Superior sagittal sinus (SSS) and cortical veins (CV) involvement were the most common sites of thrombosis and the mostly related etiology were found puerperium in seizure group (30.3 % vs 13.9 %). Patients with seizures had worse outcome in the first month of the disease (p < 0.001) but these did not have any influence thereafter. Conclusions: In this largest CVST cohort (VENOST) reported female sex, presence of focal neurological deficits and altered consciousness, thrombosis of the SSS and CVs, hemorrhagic infarction were risk factors for ES occurrence in patients with CVST.
Keywords: Cerebrovascular disease; Cerebral venous sinus thrombosis; Epilepsy; Early seizure